Dermoscopic findings in extragenital lichen sclerosus - Anna Jędrowiak; Aleksandra Kobusiewicz; Ewa Trznadel-Grodzka; Andrzej Kaszuba (Our Dermatology Online, 2018)
Lichen sclerosus (LS), also known as lichen sclerosus et atrophicus is a chronic inflammatory dermatosis of unknown aetiology. It has both genital and extragenital presentations, nevertheless genital forms significantly outnumber extragenital LS. Dermoscopy is noninvasive diagnostic tool traditionally employed in pigmented lesions, however its usefulness in inflammatory skin conditions is becoming continuously more meaningful. Although the clinical diagnosis of fully developed LS rarely causes difficulties, unusual presentations require differentiation from the diseases such as lichen planus, morphea, extramammary Paget disease, SCC and others. In these cases histopathology contributes to the diagnosis. Studies on the use of dermoscopy in LS are sparse, nevertheless some dermoscopic features of LS has been described.